2010
DOI: 10.1111/j.1469-8137.2010.03432.x
|View full text |Cite
|
Sign up to set email alerts
|

EgMYB1, an R2R3 MYB transcription factor from eucalyptus negatively regulates secondary cell wall formation in Arabidopsis and poplar

Abstract: Summary• The eucalyptus R2R3 transcription factor, EgMYB1 contains an active repressor motif in the regulatory domain of the predicted protein. It is preferentially expressed in differentiating xylem and is capable of repressing the transcription of two key lignin genes in vivo.• In order to investigate in planta the role of this putative transcriptional repressor of the lignin biosynthetic pathway, we overexpressed the EgMYB1 gene in Arabidopsis and poplar.• Expression of EgMYB1 produced similar phenotypes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(149 citation statements)
references
References 58 publications
3
142
0
4
Order By: Relevance
“…In contrast, no orthologs corresponding to the MYB factors AtMYB58 or AtMYB63 directly implicated in the regulation of lignin biosynthesis (Zhou et al, 2009) were differentially regulated. We also identified a MYB TF transcript that was significantly more abundant in stem outer tissues and belongs to subgroup 4, which includes repressors of the lignin biosynthetic pathway such as AtMYB4, EgMYB1, and ZmMYB31/42 (Jin et al, 2000;Fornalé et al, 2006Fornalé et al, , 2010Legay et al, 2010). Although functional analyses are obviously necessary, the expression of a potential lignin repressor in outer tissues is consistent with the hypolignified nature of this tissue.…”
Section: Hypolignification In Flax Stems Involves Differential Expresmentioning
confidence: 62%
“…In contrast, no orthologs corresponding to the MYB factors AtMYB58 or AtMYB63 directly implicated in the regulation of lignin biosynthesis (Zhou et al, 2009) were differentially regulated. We also identified a MYB TF transcript that was significantly more abundant in stem outer tissues and belongs to subgroup 4, which includes repressors of the lignin biosynthetic pathway such as AtMYB4, EgMYB1, and ZmMYB31/42 (Jin et al, 2000;Fornalé et al, 2006Fornalé et al, , 2010Legay et al, 2010). Although functional analyses are obviously necessary, the expression of a potential lignin repressor in outer tissues is consistent with the hypolignified nature of this tissue.…”
Section: Hypolignification In Flax Stems Involves Differential Expresmentioning
confidence: 62%
“…Statistical significance was calculated with Student's t test (*P < 0.05; **P < 0.01) precursors of other compounds such as flavonoids, and so a greater accumulation of these compounds in cork cannot be ruled out. Interestingly, the putative ortholog of Arabidopsis AtMYB4 or Eucalyptus EgMYB1, a well-known repressor of the phenylpropanoid metabolism and lignin biosynthesis (Jin et al 2000;Legay et al 2010), is strongly downregulated in cork. The downregulation of this repressor gene in cork oak agrees with the upregulation of phenylpropanoid biosynthetic enzymes such as PAL, C4H and 4CL in the same tissue, similarly as Cavallini et al (2015) found in petunia petals overexpressing MYB4.…”
Section: Discussionmentioning
confidence: 99%
“…1A). In the lignin or phenylpropanoid repressor MYBs such as AtMYB4 and Eucalyptus gunnii EgMYB1 (Jin et al, 2000;Legay et al, 2010), a zinc-finger motif (CX1-2CX7-12CX2C) and a C4 motif (FLGLx4-7V⁄LLD⁄GF⁄YR⁄Sx1LEMK) were present. These motifs were not found in FaMYB1, VvMYBC2-L1, PhMYB27, and the new poplar MYBs.…”
mentioning
confidence: 99%